2022
DOI: 10.7759/cureus.30196
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Endoscopic Retrograde Cholangiopancreatography (ERCP) Versus Endoscopic Ultrasound-Directed Transgastric ERCP in Patients With Roux-en-Y Gastric Bypass: A Systematic Review and Meta-Analysis

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is a therapeutic procedure for skilled endoscopists that can be even more challenging in some situations, including patients' post-Roux-en-y Gastric Bypass (RYGB) surgery. There is still no consensus on whether laparoscopic-assisted ERCP (LA-ERCP) or endoscopic ultrasound (EUS)-directed transgastric ERCP (EDGE) is the most appropriate, safe, and feasible approach in patients with this type of post-surgical anatomy. This systematic review and meta-analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The EDGE procedure is quickly replacing laparoscopic-assisted ERCP due to its entirely endoscopic approach, acceptable risk profile, and technical success rates in the 90% to 100% range . Moreover, in retrospective studies, the EDGE procedure has been found to have similar rates of stone clearance and adverse events as laparoscopic common bile duct exploration . During the EDGE procedure, endoscopic access to the remnant stomach is achieved by creating a gastro-gastric or jejunal-gastric fistula via a temporary lumen apposing metal stent (Figure 3).…”
Section: Discussion and Observationsmentioning
confidence: 99%
“…The EDGE procedure is quickly replacing laparoscopic-assisted ERCP due to its entirely endoscopic approach, acceptable risk profile, and technical success rates in the 90% to 100% range . Moreover, in retrospective studies, the EDGE procedure has been found to have similar rates of stone clearance and adverse events as laparoscopic common bile duct exploration . During the EDGE procedure, endoscopic access to the remnant stomach is achieved by creating a gastro-gastric or jejunal-gastric fistula via a temporary lumen apposing metal stent (Figure 3).…”
Section: Discussion and Observationsmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS), the standard modalities for the diagnosis and management of PB pathologies, are challenging or unfeasible in patients with SAA [15]. Traditional endoscopic modalities for the management of these patients have included enteroscopy-assisted ERCP (e-ERCP) [16], EUS-guided biliary drainage [17], or the more invasive laparoscopic-assisted ERCP (LA-ERCP) [18]. The decision is often guided by the type of the SAA and the anatomic consideration, available expertise, and the scope of the anticipated therapeutic interventions [17].…”
Section: Pancreaticobiliary Interventionsmentioning
confidence: 99%
“…Interventional radiologists can use a percutaneous rendezvous technique to access the biliary tree with or without concurrent ERCP. In centers without this expertise or after failure of these attempts, a laparoscopically assisted transgastric ERCP is an excellent option that can readily be performed by any surgeon with basic laparoscopic skills in concert with their interventional gastroenterologist 67,68 . The distal greater curve of the gastric remnant is mobilized, and an anterior 1 to 2 cm gastrotomy is created to facilitate passage of the endoscope into the remnant (Fig.…”
Section: Gastric Bypass Complicationsmentioning
confidence: 99%